2002
DOI: 10.1007/s00384-001-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of cytochrome P450 2E1, glutathione S-transferase M1 and T1, and susceptibility to gastric carcinoma in Taiwan

Abstract: Our findings suggest that the CYP2E1 genotype is a determinant of GC risk in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 26 publications
3
34
0
2
Order By: Relevance
“…21 Other studies, some of which were hospitalbased and mostly carried out in Asian populations, have shown that GST null genotypes did not contribute to an increased GC risk. 24,[27][28][29] Our analyses did not show any evidence of increased GC risk among subjects with GSTM1 null genotype, while a borderline significant association between the GSTT1*0/0 and increased GC risk emerged in uni-and multivariate analyses adjusted for possible confounders, as reported by previous studies. 18,19 The risk associated with the GSTT1 null genotype tended to vary also with age at diagnosis, with a higher risk at younger ages.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…21 Other studies, some of which were hospitalbased and mostly carried out in Asian populations, have shown that GST null genotypes did not contribute to an increased GC risk. 24,[27][28][29] Our analyses did not show any evidence of increased GC risk among subjects with GSTM1 null genotype, while a borderline significant association between the GSTT1*0/0 and increased GC risk emerged in uni-and multivariate analyses adjusted for possible confounders, as reported by previous studies. 18,19 The risk associated with the GSTT1 null genotype tended to vary also with age at diagnosis, with a higher risk at younger ages.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand several studies, mostly carried out in Asian populations (for which a higher prevalence of the GSTT1 null genotype has been reported), did not find any association between the GST null genotypes and increased GC risk. [24][25][26][27][28][29] Recently, a strong significant association between the GSTT1 null genotype and increased risk of another gastric neoplasia (marginal zone lymphoma) was observed in a case-control study carried out in England. 30 The interaction between GSTM1 and GSTT1 null genotypes has only been explored in 2 studies, with no evidence of departure from a multiplicative model, possibly because of the small size (91 and 136 GC cases, respectively).…”
mentioning
confidence: 99%
“…However, Nishimoto et al, (2000) suggests that the CYP2E1 RsaI variant genotype is associated with a reduced risk of upper gastrointestinal tract cancers. Wu et al, (2002) found an association of gastric cancer with CYP2E1 RsaI, but not with CYP2E1 DraI. Earlier, in a meta-analysis, Boccia et al, (2007) concluded that CYP2E1-PstI/RsaI polymorphism may be a risk factor for gastric cancer in Asian populations.…”
Section: Discussionmentioning
confidence: 98%
“…Por otro lado, para el genotipo de deleción de GSTT1 no se encontró asociación con cáncer gástrico (17,4% en los casos y 14,6% en los controles). Los estudios que han investigado también la relación de GSTT1 y cáncer gástrico han arrojado igualmente resultados conflictivos (13,22,29,(33)(34)(35)(36). Esto puede deberse al efecto combinado de la variación en la frecuencia de estos polimorfismos entre diferentes grupos étnicos (37) y la exposición a distintos factores ambientales sobre los cuales actúa la GST.…”
Section: Discussionunclassified